Evaluation of Potential Ecological Risk Index of Toxic Metals Contamination in the Soils - Arnab Saha; Bhaskar Sen Gupta; Sandhya Patidar; Nadia Martínez-Villegas (Chemistry Proceedings, 2022)
Toxic metal pollution in soil and the associated health risk is a global problem, with the majority of cases occurring in developing nations. The current work focuses on a contaminated site in Mexico which is used for recreational purposes. The contaminated site in Cerrito Blanco in San Luis Potosi, Mexico is close to an abandoned mining area surrounded by non-cultivated farmland. Analyses of topsoil samples indicated the presence of arsenic (As), copper (Cu), nickel (Ni), lead (Pb), and zinc (Zn). This work has estimated the potential harmful impacts of toxic metals by using the Contamination factor (Cf), Ecological risk factor (Er), and Potential ecological risk index (RI) by Hakanson’s method. The results indicated that the soil contamination factors (Cf) of toxic metals were: As > Zn > Cu > Pb > Ni. It is concluded that Cu, Pb, and Zn have been found in the soil samples because of past mining activities. The highest contamination factor (Cf) of As (11.94 mg/kg) in the soil was in the extremely high contamination category. It is also believed that the As concentration in the soil was high because arsenic-contaminated water was regularly used to irrigate the land. The Ecological risk factors (Er) for toxic metals were: As > Cu > Pb > Zn > Ni. In the surface soils of this region, As was a considerable ecological concern and contributed the most to potential ecological risk indices (RI). It is also acknowledged that various anthropogenic factors contributed significantly to the potential ecological risk index (RI). The spatial distribution of toxic metal contamination in the soil was also mapped using a Geographic Information System (GIS). This study concludes that a regular assessment is needed to estimate the risk level of toxic metal contamination in soil.